2023
DOI: 10.3390/polym15040815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Mouthwashes on the Surface Microhardness and Color Stability of Dental Nanohybrid Resin Composite

Abstract: Background: Surface microhardness and color stability of dental restorative material should be sustained throughout its functional lifetime to maintain the esthetic quality of the restoration. However, the frequent application of mouthwash may affect their surface microhardness and color stability. The aim of this study was to evaluate the effects of different types of mouthwashes with different contents on surface microhardness and color stability of dental nanohybrid resin-based composite. Methods: Disc spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
2
8
1
Order By: Relevance
“…[17] Also, the current study in accordance with Hamdy TM et al who studied the effect of different mouthwashes on the surface microhardness and color stability of dental nanohybrid resin composite and found that mouthwashes chemical composition had a strong effect on the surface hardness of resin composite materials. [22] The results of current study disagreed with Bohner et al who evaluated the surface roughness of resin composite and ceramic material after immersion in mouthwashes and concluded that mouthwashes did not have signi cant change in surface roughness of composite resin and ceramic materials. [23] Repolishing is critical for smooth surface, less plaque retention, facilitates hygiene, more esthetic, decrease tissue in ammation and comfortable surface of restoration.…”
Section: Discussioncontrasting
confidence: 99%
“…[17] Also, the current study in accordance with Hamdy TM et al who studied the effect of different mouthwashes on the surface microhardness and color stability of dental nanohybrid resin composite and found that mouthwashes chemical composition had a strong effect on the surface hardness of resin composite materials. [22] The results of current study disagreed with Bohner et al who evaluated the surface roughness of resin composite and ceramic material after immersion in mouthwashes and concluded that mouthwashes did not have signi cant change in surface roughness of composite resin and ceramic materials. [23] Repolishing is critical for smooth surface, less plaque retention, facilitates hygiene, more esthetic, decrease tissue in ammation and comfortable surface of restoration.…”
Section: Discussioncontrasting
confidence: 99%
“…The statistical difference between the three groups was substantial, and the p-value was 0.001. These results were in agreement with the studies of Hamdy et al (2023) and Abdallah et al (2021), where authors in their findings reported that pH largely affects the solubility and hardness of different esthetic restorative materials with different filler sizes.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results of this study, a systematic review stated that color change after treatment with mouthwashes was considered clinically acceptable (de Morais Sampaio et al, 2021). A study comparing the color stability of nanohybrid composites after treatment with different mouthwashes (Chlorohexidine, Listerine Green Tea, and Colgate Optic White Whitening Mouthwash), reported an acceptable color change in specimens treated with the mouthwash containing a whitening component (Hamdy et al, 2023).…”
Section: Discussionsupporting
confidence: 78%
“…Solidex finishing and polishing kit (Shofu Inc., Kyoto, Japan) was used for SDX specimens. Finally, the specimens were post-polymerized in distilled water at 37 C for 24 h (Hamdy et al, 2023).…”
Section: Introductionmentioning
confidence: 99%